PENERAPAN SYSTEM DEVELOPMENT LIFE CYCLE DALAM APLIKASI PEMESANAN LAPANGAN FUTSAL BERBASIS WEB - Yulia, Ratih; Hernawan, Arbi Rafli (LPPM Universitas Bina Sarana Informatika, 2021)
Futsal sport is currently in great demand by the public, especially for youth who like sports. Futsal is performed on a smaller field compared to football. Futsal is played in a team with 5 members consisting of players and goalkeepers. Many people start looking for this futsal sport by visiting the futsal place to find information about the field and the booking schedule. Sometimes this way of ordering makes people feel difficult, because they have to come first and then look for an empty schedule or it turns out that the booking schedule is full. This is very ineffective and inefficient in service for tenants and owners, because there is no internet-based information system. In this study, aims to create a web-based futsal field ordering application by implementing a development life cycle (SDLC) system to overcome existing problems making it easier for tenants to get information about the futsal field, field booking information, and more effectively and efficiently in terms of time. In addition, futsal field owners can also manage futsal field transaction data accurately